2023
DOI: 10.1038/s41398-023-02623-y
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic models predicting transition to psychotic disorder using blood-based biomarkers: a systematic review and critical appraisal

Jonah F. Byrne,
David Mongan,
Jennifer Murphy
et al.

Abstract: Accumulating evidence suggests individuals with psychotic disorder show abnormalities in metabolic and inflammatory processes. Recently, several studies have employed blood-based predictors in models predicting transition to psychotic disorder in risk-enriched populations. A systematic review of the performance and methodology of prognostic models using blood-based biomarkers in the prediction of psychotic disorder from risk-enriched populations is warranted. Databases (PubMed, EMBASE and PsycINFO) were search… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 75 publications
0
1
0
Order By: Relevance
“…A recent systematic review 21 found that while several different prognostic models have been developed to predict psychosis among individuals with CHR symptoms using proteomic, lipidomic, or genetic data, 13 , 19 , 22–24 there has been limited replication of findings or external validation of models, which has been recognized as an important limitation in the field. 21 , 25 , 26 Using a large multi-study population, we aimed to clarify the potential of plasma proteins, quantified using proteomic methods, to predict transition to psychosis among individuals at CHR. We hypothesized that an a priori - specified prediction model would have a strong predictive ability for psychosis risk.…”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review 21 found that while several different prognostic models have been developed to predict psychosis among individuals with CHR symptoms using proteomic, lipidomic, or genetic data, 13 , 19 , 22–24 there has been limited replication of findings or external validation of models, which has been recognized as an important limitation in the field. 21 , 25 , 26 Using a large multi-study population, we aimed to clarify the potential of plasma proteins, quantified using proteomic methods, to predict transition to psychosis among individuals at CHR. We hypothesized that an a priori - specified prediction model would have a strong predictive ability for psychosis risk.…”
Section: Introductionmentioning
confidence: 99%